Applied economics - Griffiths, Alan; Wall, Stuart (London, 1984)
Recent changes in UK economic structure are covered in this study of the application of basic economic analysis to the central economic problems of the time. Guidance about methods of applying economic theory is given and it aims to combine information with analysis in over 27 separate topic areas, examining the major economic issues arising within each topic area. Although focusing on the UK, reference is made throughout to the experience of the other advanced industrialized countries, so helping the reader place any observations on the UK in a broader international context. "Applied Economics" is designed for undergraduate students in the first and second years of degree courses in economics, the social sciences and business studies and for those taking professional courses with an economic content. The material may also be useful to many involved in Higher and National Diplomas and Certificates of the BTEC and to serious A level students.
Keywords: Economics